Cameroon : Selected Issues. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2015)
This Selected Issues paper examines recent performance and reform agenda for Cameroon's state-owned enterprises (SOEs). Cameroon's SOEs are important providers of formal employment and have a large weight in the economy. The profitability and financial autonomy of SOEs have deteriorated in recent years, draining scarce budget resources. In addition, SOEs have amassed significant contingent liabilities in the form of debt and arrears. Weak corporate governance is a key factor in SOEs' poor performance. The reform agenda should include enhancing the monitoring of SOEs, improving disclosure of their contingent liabilities, and strengthening their governance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet